Stability analysis and stabilization control of a grid-forming VSC-HVDC system - Lu, Yi; Shi, Gang; Chen, Qian; Qiu, Peng; Zhou, Jianqiao; Yang, Renxin; Zhang, Jianwen (Frontiers in Energy Research, 2024)
As the penetration of the integrated intermittent and fluctuating new energy (e.g., wind and photovoltaic power) increases, the conventional grid-following voltage source converter (VSC)-based high voltage direct current (HVDC) transmission system faces the problem of interactive instability with the grid. A novel grid-forming control strategy is proposed to overcome these issues, which adopts the dynamics of a DC capacitor to realize the function of self-synchronization with the grid. Moreover, the per-unit DC voltage can automatically track the grid frequency, acting as a phase-locked loop. Next, the small-signal model of the grid-forming VSC-HVDC system is established, and the stability of the system is analyzed using the eigenvalue analysis method and the complex power coefficient method. In addition, the stabilization controller is proposed for the grid-forming (GFM) control structure, which further enhances the grid-forming VSC-HVDC system’s stability and helps it operate stably under both stiff and weak grid conditions. Research results show that the VSC-HVDC system under the proposed grid-forming control can work stably in both stiff and weak grids. The grid-forming VSC-HVDC system is robust and can maintain stable operations with a large range variation of the parameters in the current and voltage control loop. Simulations are carried out on the PSCAD/EMTDC platform to verify the proposed grid-forming control strategy.